2008
DOI: 10.2174/1874241600801010079
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) - Structure, Epidemiology, Function and Diagnostics of a Cardiovascular Risk Marker

Abstract: Decades after its first description by Berg 1963 lipoprotein(a) (Lp(a)) is an established risk marker of cardiovascular diseases which is independent from other risk markers. The main difference of Lp(a) compared to LDL is the apo(a) residue which is covalently bound to apoB. Apo(a) is a glycoprotein which underlies a large genetic polymorphism. The latter is caused by a variation of the kringle-IV-type-2 repeats of the protein which is characterized by a large structural homology to plasminogen. The Lp(a) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 211 publications
(214 reference statements)
0
13
0
Order By: Relevance
“…It was initially thought that LDL receptor (LDLR) in the liver is responsible for the degradation of Lp(a). However, there is evidence that LDLR has minimal or no effect on Lp(a) catabolism [20]. Many kinetic studies have reported that Lp(a) has a longer circulating time than does LDL-C due to the small affinity of Lp(a) for LDLR [17,20].…”
Section: E Livermentioning
confidence: 99%
See 3 more Smart Citations
“…It was initially thought that LDL receptor (LDLR) in the liver is responsible for the degradation of Lp(a). However, there is evidence that LDLR has minimal or no effect on Lp(a) catabolism [20]. Many kinetic studies have reported that Lp(a) has a longer circulating time than does LDL-C due to the small affinity of Lp(a) for LDLR [17,20].…”
Section: E Livermentioning
confidence: 99%
“…However, there is evidence that LDLR has minimal or no effect on Lp(a) catabolism [20]. Many kinetic studies have reported that Lp(a) has a longer circulating time than does LDL-C due to the small affinity of Lp(a) for LDLR [17,20]. is low affinity occurs because the apo(a) component interferes with the positioning of the LDLR [17].…”
Section: E Livermentioning
confidence: 99%
See 2 more Smart Citations
“…It has tendency to attract other Lp(a) particles, trap LDL, VLDL, blood infiltrates and calcium forming atheromatous plaque in response to vessel injury. Antifibrinolytic activity and adhesiveness makes it much more atherogenic than LDL [8].…”
Section: Introductionmentioning
confidence: 99%